How do elite soccer teams perform to ball recovery? Effects of tactical modelling and contextual variables on the defensive patterns of play - Fernandes, T.; Camerino, O.; Garganta, J.; Hileno, R.; Barreira, D. (Journal of Human Kinetics, 2020)
Researchers in soccer match analysis have been using limited procedures to express the dynamics of the game and mainly focus on the attack. Therefore, the aims of this paper were to detect the successful teams` ball recovery defensive patterns of play and study the influence of tactical modelling, halves, match status, opponent quality and stage competition on those patterns. The sample consisted of 1323 situations of defensive ball possession of the semi-finalist teams from the 2014 FIFA World Cup play-offs, which was collected by a valid and reliable observational instrument (Soccer-Defence). The Kruskal-Wallis H, Mann-Whitney U, Chi-square, Z-, multinomial logistic regression tests and sequential analysis (p < .05; z > 1.96) were used accordingly to test the differences and associations among and within teams of tactical modelling, tactical-technical behaviours and contextual variables to ball recovery. We found that among teams ball recovery differed in duration; H(3) = 14.958, p = .002. Germany were more likely to perform ball recovery by the goalkeeper than Argentina (p = .04; OR = 0.47) or the Netherlands (p < .05; OR = 0.50). Nevertheless, Brazil was the least likely to concede a shot off goal. Teams facing lower-ranked opponents were 0.63 times less likely to perform ball recovery by interception (p <.001). Additionally, sequential analysis illustrated that teams varied between central and lateral high-pressure zones before ball recovery in lower zones of the field. Finally, coaches could use such findings to design training exercises, create their own style of play, and set strategies.